Green Synthesis of Copper Oxide Nanoparticles Using Eichhornia Crassipes Leaf Extract, its Antibacterial and Photocatalytic Activities - Saligedo, Tamene S.; Muleta, Gutta G.; Tsega, Tilahun W.; Tadele, Kirubel T. (Current Nanomaterials, 2023)
Background: Green approach is among the preferable methods for metal-based nanoparticles synthesis due to its simplicity, cost-effectiveness, eco-friendly reagents, and a broad spectrum of biological activities. This study aimed to synthesize copper oxide nanoparticles using Eichhornia Crassipes (Water hyacinth) leaf extract in an eco-friendly manner. Methods: Copper oxide nanoparticles were synthesized using Eichhornia Crassipes (Water hyacinth) leaf extract. The effect of different parameters, such as concentration of the plant extract, time, light, and pH, on the formation of the nanoparticles was investigated. The synthesized nanoparticles were characterized by UV-Vis, FTIR, TEM, and P-XRD spectroscopic techniques. The antibacterial and photocatalytic activities of the synthesized copper oxide nanoparticles were determined. Results: Powder X-Ray diffraction analysis (PXRD) showed that the copper oxide nanoparticles have a size of 9.1 nm. Transmission electron microscopy (TEM) images displayed that the Nps were spherical, polydispersed, and well crystallized. The nanoparticles displayed good antibacterial activity against Escherichia coli, Staphylococcus, Bacillus subtilis, and Salmonella typhi, with the highest activity against Salmonella typhi. Conclusion: Copper oxide nanoparticles were effectively synthesized, and secondary metabolites, such as flavonoids, alkaloids, tannins, and phenols, acted as both capping and stabilizing agents. The good antibacterial and photocatalytic activities of the synthesized nanoparticles indicated their potential for applications in pharmacology and environmental protections, respectively. However, the product needs further investigation to enhance its antibacterial potential for efficient pharmacological application.
Keywords: Eichhornia crassipes